1989
DOI: 10.1007/bf02464916
|View full text |Cite
|
Sign up to set email alerts
|

Extremely large chromosomal deletions are intimately involved in genetic instability and genomic rearrangements inStreptomyces glaucescens

Abstract: Genetic instability in Streptomyces glaucescens characteristically involves the occurrence of gross genomic rearrangements including high-level sequence amplification and extensive deletion. We investigated the relationship of the unstable melC and strS loci and a 100 kb region of the chromosome which frequently gives rise to intense heterogeneous DNA amplification. Standard chromosome walking using a cosmid bank in conjunction with a "reverse-blot" procedure enabled us to construct a contiguous genomic BamHI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
2

Year Published

1990
1990
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 51 publications
0
35
2
Order By: Relevance
“…The association between deletion and genetic instability was frequently reported in Streptomyces species (2,5,6). In S. glaucescens, for example, the double mutant phenotype Str-Mel-was ascribed to deletions whose sizes were estimated to range from 270 to over 800 kb (2).…”
mentioning
confidence: 99%
“…The association between deletion and genetic instability was frequently reported in Streptomyces species (2,5,6). In S. glaucescens, for example, the double mutant phenotype Str-Mel-was ascribed to deletions whose sizes were estimated to range from 270 to over 800 kb (2).…”
mentioning
confidence: 99%
“…Interestingly, in this species the resulting genetic map (20) could not easily be reconciled with subsequently obtained physical linkage data, which clearly showed that the two loci are 350 kb apart (7). Although both map to the chromosome, the apparent map interval derived from recombination frequencies suggested a substantially larger distance than this, indicating that even apparently reliable mapping data must be viewed with the utmost caution when unstable traits are involved.…”
Section: Genetic Instabilitymentioning
confidence: 67%
“…22,23,28). Additionally, analyses involving DNA surrounding unstable genes demonstrated that extensive flanking sequences were also absent, implicating large chromosomal deletion events in the instabilities (6,7,18). In S. glaucescens, deletions which were responsible for the loss of the unstable genes coding for tyrosinase (melC) and hydroxystreptomycin phosphotransferase (strS) were initially characterized (22,23).…”
Section: Chromosomal Deletionmentioning
confidence: 99%
See 2 more Smart Citations